Evaluation of an open access echocardiography service in the Netherlands: a mixed methods study of indications, outcomes, patient management and trends - Streppel Marjolijn; Lodewijks-van der Bolt Cara LB; Tent Marleen; Baur Leo HB; van Heur Leanne MSG; Winkens Ron AG; Stoffers Henri EJH (BMC, 2010)
Abstract Background In our region (Eastern South Limburg, The Netherlands) an open access echocardiography service started in 2002. It was the first service of this kind in The Netherlands. Our study aims were: (1) to evaluate demand for the service, participation, indications, echocardiography outcomes, and management by the general practitioner (GP); (2) to analyse changes in indications and outcomes over the years. Methods (1) Data from GP request forms, echocardiography reports and a retrospective GP questionnaire on management (response rate 83%) of 625 consecutive patients (Dec. 2002 - March 2007) were analysed cross-sectionally. (2) For the analysis of changes over the years, data from GP request forms and echocardiography reports of the first and last 250 patients that visited the service between Dec. 2002 and Feb. 2008 (n = 1001) were compared. Results The echocardiography service was used by 81% of the regional GPs. On average, a GP referred one patient per year to the service. Intended indications for the service were dyspnoea (32%), cardiac murmur (59%), and peripheral oedema (17%). Of the other indications (22%), one-third was for evaluation of suspected left ventricular hypertrophy (LVH). Expected outcomes were left ventricular dysfunction (LVD) (43%, predominantly diastolic) and valve disease (25%). We also found a high proportion of LVH (50%). Only 24% of all echocardiograms showed no relevant disease. The GP followed the cardiologist's advice to refer the patient for further evaluation in 71%. In recent patients, more echocardiography requests were done for 'cardiac murmur' and 'other' indications, but less for 'dyspnoea'. The proportions of patients with LVD, LVH and valve disease decreased and the proportion of patients with no relevant disease increased. The number of advices by the cardiologists increased. Conclusion Overall, GPs used the open access echocardiography service efficiently (i.e. with a high chance of finding relevant pathology), but efficiency decreased slightly over the years. To meet the needs of the GPs, indications might be widened with 'suspicion LVH'. Further specification of the indications for open access echocardiography - by defining a stepwise diagnostic approach including ECG and (NT-pro)BNP - might improve the service.